Biomedical image registration : 8th International Workshop, WBIR 2018, Leiden, the Netherlands, June 28-29, 2018, Proceedings /: 8th International Workshop, WBIR 2018, Leiden, the Netherlands, June 28-29, 2018, Proceedings. (2018) - Unknown
No abstract available